Rekonsiliasi sebagai Strategi Penyelesaian Konflik Keluarga dalam Perspektif Manajemen Konflik - Dyah Lauren Pitaloka; Dea Riswandasari; Pudenta Helda; Fioren Dwika Maharani; Fajar Saefuloh; Yumi Hartati; Saliman Saliman (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Reconciliation is viewed as an effective method for managing conflicts since it focuses on dialogue, mediation, and resolving disputes through peaceful means. This study aims to examine the role of reconciliation in addressing family conflicts from the perspective of conflict management. The research employs a literature review approach by analyzing journal articles, books, news reports, and other relevant sources related to reconciliation, mediation, conflict resolution, and peace education. The findings reveal that reconciliation contributes significantly to reducing prolonged conflicts, improving communication, rebuilding trust, and strengthening positive relationships among family members. Mediation and family-centered approaches play an essential role in facilitating the reconciliation process by encouraging dialogue, mutual respect, and shared understanding between conflicting parties. Furthermore, peace education supports the reconciliation process by helping individuals overcome emotional trauma, develop empathy, and increase awareness of the importance of maintaining harmonious and non-violent relationships within the family. The study also highlights that sustainable reconciliation requires active participation and commitment from all family members. Therefore, reconciliation can be regarded as an important strategy for managing family conflicts because it emphasizes communication, compassion, cooperation, and peaceful problem-solving to achieve long-term family harmony and social well-being.